Formation of Mixed‐Valence Luminescent Silver Clusters via Cation‐Coupled Electron‐Transfer in a Redox‐Active Ionic Crystal Based on a Dawson‐type Polyoxometalate with Closed Pores. Issue 16 (18th March 2021) - Haraguchi, Naoya; Okunaga, Tomoki; Shimoyama, Yuto; Ogiwara, Naoki; Kikkawa, Soichi; Yamazoe, Seiji; Inada, Miki; Tachikawa, Takashi; Uchida, Sayaka
Abstract: A redox‐active ionic crystal based on a Dawson‐type polyoxometalate (POM) [α‐P2 W VI 18 O62 ] 6− is utilized to form and stabilize small mixed‐valence luminescent silver clusters without the aid of protecting ligands at room temperature. A reduced ionic crystal of Cs3 H5 [Cr3 O(OOCH)6 (etpy)3 ]3 [α‐P2 W V 5 W VI 13 O62 ] ⋅ 5H2 O (etpy=4‐ethylpyridine) is formed by a cation‐coupled electron‐transfer (CCET) reaction with sodium ascorbate as a reducing reagent to provide electrons and Cs + as counter cations of POM. Then, silver is introduced via ion‐exchange between Cs + and Ag + jointly with CCET reaction: X‐ray photoelectron spectroscopy and elemental analysis show that the ionic crystal is oxidized via electron‐transfer from the POM (W 5+ ) to Ag +, and [Ag 0 1.5 Ag I 1.5 ]H4.5 [Cr3 O(OOCH)6 (etpy)3 ]3 [α‐P2 W V 3 W VI 15 O62 ] ⋅ 7H2 O is formed. Photoluminescence and X‐ray absorption fine structure suggest that the silver species exist as mixed‐valence luminescent clusters with an average formula of [Ag4 ] 2+ probably in a tetrahedral geometry. Abstract : A redox‐active ionic crystal based on a Dawson‐type polyoxometalate [α‐P2 W V n W VI 18− n O62 ] (6+ n )− is utilized to form and stabilize small mixed‐valence luminescent silver clusters without the aid of protecting ligands. Photoluminescence and X‐ray absorption fine structure measurements suggest that clusters with an average formula of [Ag4 ] 2+ are formed via a cation‐coupled electron‐transfer reaction in the closed pores of the ionic crystal.